Teaching Kindergarten Student using Augmented Reality - Deshmukh, SS; Gaikwad, Akshay; Mahajan, Mukesh; Bonde, Harshali; Kolge, Sanjana (International Journal of Computer Sciences and Engineering, 2025)
Our research goal is to develop an augmented reality application to improve the learning experience of the kindergarten students. We are developed an android application which includes augmented reality features which will help kindergarten students learn things in more easy and interesting way. This application scans the environment using device camera and search for markers. If Marker is detected it shows the 3D model corresponding to that marker. OpenCV includes algorithms of feature detection. We used natural feature detection with some improvement. Natural feature detection algorithms help to identify images or markers. This algorithm good for capturing and detecting images with greater accuracy and speeds. This project proposes a method for teaching early childhood kindergarten students by designing augmented reality. With the help of AR technology to generate learning interest in kindergarten students.